PECULIARITIES OF BUILDING OF MEDICAL TERMS IN ENGLISH - Самойленко, Елена (SWorldJournal, 2021)
The article is devoted to the special features of the Ukrainian medical terminology connected with word-building. The article has analyzed peculiarities of different ways of word-building: both prefixal-suffixal and compounding. A lot of attention is pai